Effectiveness of a Planned Educational Program on Post-Mastectomy Exercises to Enhance Shoulder Functioning Among Breast Cancer Survivors - Ali Kadhim, Rusul; Wanas Khudiar, Fatima (Journal of Neonatal Surgery, 2025)
Background: Breast cancer is a prevalent and life-threatening disease worldwide, causing high morbidity and mortality rates among women. Exercises for patients who are having a mastectomy are very crucial. Therefore, an effective postoperative exercise program is needed to improve shoulder function and prevent impairments of the upper limb and limitations in activities of daily living. This study aims to investigate the effectiveness of an educational program on shoulder functions among women undergoing mastectomy. Methodology A quasi-experimental design was used to achieve the study objectives at the National Cancer Teaching Hospital in Al-Najaf City. (60) patients divided into (30) control group and (30) experimental group who underwent mastectomy were identified according to specific criteria to participate in the study. Pre-test and one post-test were collected for all patients with mastectomy to evaluate the effectiveness of the exercise program on shoulder function. Result: Most participants were aged (49-74) years (58.33%), married (90%), and housewives (78.3%). The study population showed early menarche (61.67%) at (10-12) years, marriage between (15-25) years (68.33%), high parity (53.33%) had (4-6) children, and high prevalence of breastfeeding (68.33%). Most cancer incidents occurred during the pre-menopausal period (58.33%). These findings support the implementation of structured educational interventions to improve shoulder function among women undergoing mastectomy. In addition, the results revealed that a post-mastectomy exercise program implemented in participants had multiple benefits and positive effects for improving shoulder function, faster physical recovery, and improved range of motion necessary for daily activities. Conclusion: The performance of exercise had an effective role in helping breast cancer patients improve and recover shoulder function through a scientific and rational exercise program of the experimental group compared with the control group.